التأويل بين التراث العربي والدراسات الغربية الحديثة (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Interpretation Had Got A Great Care Throught The Different Humain Civilizations From Greece And Old Arabs To The Western Students, It Was Necessery To Understand The Immortal Texts Because They Have More Than One Signification. The Scientific Debates Had Agreed Along The History Including Limits And Explanatory Contents, Where They Had Disagreed In Others. And From This Metter, We Wanted In This Research To Look For " The Interpretation Between The Arabian Patrimony And Modern Western Studies.                           Key words - The interpretation, The Arabian patrimony, Modern Western studies .